2016
DOI: 10.1007/s13277-016-4856-x
|View full text |Cite
|
Sign up to set email alerts
|

A headlight on liquid biopsies: a challenging tool for breast cancer management

Abstract: Breast cancer is the most frequent carcinoma and second most common cause of cancer-related mortality in postmenopausal women. The acquisition of somatic mutations represents the main mechanism through which cancer cells overcome physiological cellular signaling pathways (e.g., PI3K/Akt/mTOR, PTEN, TP53). To date, diagnosis and metastasis monitoring is mainly carried out through tissue biopsy and/or re-biopsy, a very invasive procedure limited only to certain locations and not always feasible in clinical pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 92 publications
0
13
0
Order By: Relevance
“…PIK3CA mutations are very frequent (20%-40%) genetic alterations in MBC, particularly in node-negative, ER þ and HER2 À breast cancer, and are generally related to a good clinical outcome with a lower recurrence and mortality rate (35). Nevertheless, tissue-based NGS had already demonstrated that at least 33% of TN breast cancer have deregulated PI3K/AKT pathways, making these pathways an attractive target for pharmacologic treatment (e.g., everolimus) and highlighting the importance of mutation profiling for individualized therapies (36).…”
Section: Secondary Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…PIK3CA mutations are very frequent (20%-40%) genetic alterations in MBC, particularly in node-negative, ER þ and HER2 À breast cancer, and are generally related to a good clinical outcome with a lower recurrence and mortality rate (35). Nevertheless, tissue-based NGS had already demonstrated that at least 33% of TN breast cancer have deregulated PI3K/AKT pathways, making these pathways an attractive target for pharmacologic treatment (e.g., everolimus) and highlighting the importance of mutation profiling for individualized therapies (36).…”
Section: Secondary Objectivesmentioning
confidence: 99%
“…In our population, maybe because enriched in IBC (64% of the patients), with a rate of 40% in the entire population and of 31% in the TN subgroup, PIK3CA/mTOR pathway (altered in 22 patients, including 12 patients with IBC) appears the second most altered pathway, immediately after TP53 (52% and 61%, in the entire population and TN subgroup respectively). Indeed, the mutations in the TP53 gene are relevant in breast carcinogenesis, with a frequency up to 83% in basal-like tumors (35). Among the patients with HER2 þ disease, HER2 alteration is the second most frequent.…”
Section: Secondary Objectivesmentioning
confidence: 99%
“…PI3K/AKT/mTOR (PAM) represents the main signaling pathway responsible for cell proliferation, survival, metabolism and motility regulation and is often activated in BC [ 51 - 54 ] (Figure 1 ). A heterodimeric molecule belonging to the lipid kinases, phosphoinositide 3-kinase (PI3K), is the major component of this pathway.…”
Section: Target Therapy In Tnbcmentioning
confidence: 99%
“…Therefore, the molecular analysis of the tumor and/or of the metastatic lesions is becoming more and more requested at the time of PD. Unfortunately, tissue biopsy is a procedure often limited by several features, including its invasiveness, the not easy access to different tumor sites, the high intra-tumor heterogeneity, and not ultimately the low patients' compliance [20]. Thus, in the last decade, many new noninvasive approaches have been studied to overcome the aforementioned issues.…”
Section: The Importance Of Liquid Biopsy In Nsclcmentioning
confidence: 99%